Empowering the steel industry with solar: Sustainable energy for a greener future - Farzana, Dusuki; Roziah, Zailan; Fatin Zafirah, Mansur; Khairulnadzmi, Jamaluddin (Elsevier, 2025)
Steel manufacturing is an energy-intensive industry that grappling with rising electricity costs and substantial carbon emissions. While renewable energy is gaining attention, the integration of large-scale industrial solar photovoltaic (PV) systems remains challenging due to space constraints, fluctuating energy demands, and financial limitations. Most existing research focuses on small-scale commercial and residential solar installations. It leaves a gap in large-scale industrial systems, which require customized stringing, adaptive inverter sizing, and optimized DC/AC ratios. This research explores how to design an optimized large-scale rooftop PV system for steel manufacturing to maximize performance and profitability. The methodology involves designing and simulating a 2.8 MWp rooftop solar PV system using PVsyst software. Following this, technology selection, technical performance, economic, environmental, and sensitivity analyses were conducted. The performance ratio analysis identified a 1.43 DC/AC ratio as optimal, achieving a PR of 81.67 %. A comparative analysis between self-consumption (SELCO) and Net Offset Virtual Aggregation (NOVA) demonstrated that SELCO is the superior option, yielding RM 7.87 million in annual savings with a 9.5-month payback period. Electricity consumption of 312,417.25 kWh/month contributes to a greenhouse gas emission reduction of approximately 236.81 tons CO2-eq. The sensitivity analysis revealed that as DC voltage drop increased from 2.70 % to 3.30 %, energy output declined, leading to a simultaneous rise in DC losses from 0.78 % to 1.14 %.These findings highlighted large-scale solar PV as a viable decarbonization strategy. Additionally, the design integrates technical performance, financial, and environmental factors into a holistic framework to facilitate solar PV adoption in heavy industries.